The Neutral Mask’s Phenomenology (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this article, I propose a conceptual approach between the expressive feature known as the Neutral Mask and the philosophical approach called Phenomenology. I try to describe in general terms the principles of acting with this type of mask, which was originally called Noble, and I compare its principles with some aspects of the phenomenological method. Finally, I question the relationship between actor and mask, trying to provoke the reader to question certain representational paradigms.
Keywords: Neutral Mask; Phenomenology; Masks Theater